2018
DOI: 10.1089/aid.2017.0067
|View full text |Cite
|
Sign up to set email alerts
|

“We Need to Deploy Them Very Thoughtfully and Carefully”: Perceptions of Analytical Treatment Interruptions in HIV Cure Research in the United States—A Qualitative Inquiry

Abstract: Strategies to control HIV in the absence of antiretroviral therapy are needed to cure HIV. However, such strategies will require analytical treatment interruptions (ATIs) to determine their efficacy. We investigated how U.S. stakeholders involved in HIV cure research perceive ATIs. We conducted 36 in-depth interviews with three groups of stakeholders: 12 people living with HIV, 11 clinician-researchers, and 13 policy-makers/bioethicists. Qualitative data revealed several themes. First, there was little consens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 67 publications
4
73
0
Order By: Relevance
“…The biggest difference in trade-offs was that physicians were more concerned about outcomes whereas PLWH were more concerned about their quality of life (consultation frequency and moderate SE). In line with previous research [3,12,15,18], this result might indicate that PLWH motivations to participate were more altruistic than individual. It also underlines the need for physicians to consider moderate SE and not only severe SE.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The biggest difference in trade-offs was that physicians were more concerned about outcomes whereas PLWH were more concerned about their quality of life (consultation frequency and moderate SE). In line with previous research [3,12,15,18], this result might indicate that PLWH motivations to participate were more altruistic than individual. It also underlines the need for physicians to consider moderate SE and not only severe SE.…”
Section: Discussionsupporting
confidence: 92%
“…HIV altruism is one important motivator influencing willingness to participate in HCRCT [3,12,15,18], reflecting the historical advocacy and joint mobilization of PLWH in response to HIV epidemic [1,2,20,21]. Altruistic-based benefits, such as participating in research for the benefit of future generations, have been shown to be part of the value associated with some health programmes [22][23][24].…”
mentioning
confidence: 99%
“…For example, one study performed in Thailand found that participants in HIV cure research were motivated by giving back to their community and by the potential benefits not only to themselves but also to the investigators and others with HIV 7 . Additional studies have found similar other‐oriented motivations 8 …”
mentioning
confidence: 99%
“…7 Additional studies have found similar other-oriented motivations. 8 People's willingness to take risk for an HIV cure also goes beyond the clinical or health benefit, and the fact that people living with HIV are often quite healthy does not preclude the possibility that a cure would significantly improve their overall quality of life. 9 The value of a cure may lie in quality-of-life factors such as destigmatization, liberation from concerns of transmitting HIV to others, and freedom from the burden of daily medication.…”
mentioning
confidence: 99%
“…It is well understood that initial HIV cure clinical studies will not lead to complete removal of the virus and will pose substantial risks to study participants . Some HIV cure clinical studies will require an intensively monitored ART pause (IMAP), also often referred to as analytical treatment interruption (ATI), to demonstrate efficacy of interventions .…”
Section: Introductionmentioning
confidence: 99%